A highly specific 'turn-on' fluorescent detection of Mg2+ through a xanthene based fluorescent molecular probe. Issue 8 (18th January 2016) - Pandey, Abha; Kumar, Ajit; Vishwakarma, Siddharth; Upadhyay, K. K.
Abstract : Two acid hydrazones incorporating xanthene as a metal chelating centre (B-XAN andN-XAN ) have been synthesized, characterized and evaluated for the optical sensing of Mg 2+ and Al 3+ . Abstract : Two acid hydrazones incorporating xanthene as a metal chelating centre (B-XAN andN-XAN ) have been synthesized, characterized and evaluated for the optical sensing of Mg 2+ and Al 3+ . The replacement of the naphthyl moiety inN-XAN by the phenyl moiety inB-XAN leads to total specificity of the latter one towards Mg 2+ . TheB-XAN exhibited a highly sensitive and selective 'turn-on' fluorescent response towards Mg 2+ through intense blue fluorescence enhancement. This measurement was free from any interference by other cationic analytes including the Ca 2+ and Al 3+ also. The binding constant, stoichiometry as well as the mechanistic aspect of the above sensing phenomenon were also studied through various spectroscopic methods.